Pengenalan Dasar Ekonomi Syariah Bagi Siswa SMA Nurul Hasanah - Mhd Zulkifli hasibuan; Mimi Rosadi; Alkausar Saragih; Dalyanto Dalyanto; Dian Habibi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
This Community Service aims to introduce the basic concepts of sharia economics to students at Nurul Hasanah High School. The background to this Community Service is the importance of understanding an economic system that is in accordance with sharia principles among the younger generation, especially in the school environment. Sharia economics, which is based on Islamic values such as justice, transparency and social responsibility, offers an ethical and sustainable alternative in economic management. This Community Service uses an educational approach through counseling, discussions and simulations to provide a comprehensive understanding of concepts such as usury, zakat, mudharabah and profit sharing.Community Service shows that before this program, many students had a limited understanding of sharia economics and often equated these concepts with conventional economics. After participating in the program, there was a significant increase in their understanding of the basic principles of sharia economics, as well as awareness of the importance of applying ethics and moral values in economic activities. In addition, students also show a high interest in learning more and applying these concepts in everyday life, including in personal financial management and business activities.This program is expected to be sustainable and further developed to cover other relevant topics, such as Islamic banking and halal investment, in order to equip students with in-depth knowledge and practical skills in the field of Islamic economics. Thus, this program not only contributes to increasing Islamic financial literacy among students, but also to the formation of character based on the values of justice and social welfare